Evidence of the Disproportionate Representation of Foreign Populations in Special Education in Spain: An Approach to Statistical Data - García Castaño, Javier; Goenechea Permisán, Cristina; Rubio Gómez, María (Two Homelands, 2025)
For over half a century, there has been a growing awareness of the disproportionate representation of minority students in special education systems around the world. Spain has yet to undertake an in-depth analysis of this issue. This article investigates this situation using a statistical analysis of relevant data to align with international findings. By applying a z-score to the dataset of national and foreign populations, significant differences emerge, particularly among certain nationalities. The conclusions highlight considerations for future research, emphasizing the need for a multi-situated, interdisciplinary approach to address educational inequality.